Value Analysis in Airframe Manufacturing Industry: A Value Network Approach - Diyah Ratna Fauziana; Rabiatul Adwiyah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim: To map the value network in the aircraft manufacturing industry ecosystem and to identify the fundamental values in the industry Design/Methode/Approach : A literature review was conducted on 26 research papers selected from 132 articles from Scopus and Google Scholar databases. In-depth interviews were conducted with several actors in the industry to validate the study result Research Finding: Quality, safety, and cost are the essential values in business competition, based on the industry’s long-term strategy and business objectives. Theoretical contribution/Originality: The using of network value analysis in the aircraft manufacturing industry Practitioner/Policy implication: The managerial implications of this study are in the form of strategic input for decision-makers in the industry, by understanding their roles and responsibilities in the industry value network. Research limitation: Since this study was conducted using a qualitative approach, the quantitative survey would be recommended for future study. he industry value network.